Sleep regulation in Drosophila: a review of neural circuits and genetics - Zhao, Yiyang; Zhang, Kexing; Bian, Hongsheng; Ma, Xiaoyan; Wang, Songlin; Wang, Yanyan; Yu, Shuang; Huang, Lili (Frontiers in Neuroscience, 2026)
Sleep in Drosophila melanogaster is regulated by a complex and distributed network of neural circuits that are influenced by factors such as internal state, circadian timing, and prior experiences. While no single “sleep center” has been identified, key brain regions—including the central complex, the mushroom bodies, and other associative structures—such as ventral nerve cord (VNC) contribute to the modulation of sleep and wakefulness. The roles of these regions appear to be dynamic, context-dependent, and often overlapping, reflecting the multifaceted nature of sleep regulation. At the circuit level, mechanisms such as changes in neuronal firing patterns, neurotransmitter systems (e.g., octopamine, dopamine, GABA), and experience-dependent synaptic plasticity have been shown to regulate sleep-wake cycles. On a molecular scale, a variety of genes—including shaker, fruitless, and GAT—influence sleep regulation through distinct pathways, with perturbations in these genes resulting in significant alterations in sleep duration, architecture, and homeostatic regulation. Recent studies, particularly those utilizing Drosophila sleep mutants, have provided valuable insights into the genetic and circuit-level interactions that govern sleep homeostasis and its coordination with the circadian system. These findings underscore sleep as an emergent property of interacting neural and genetic networks, providing a robust model for understanding the mechanisms of sleep in more complex organisms. This review synthesizes the latest advancements in Drosophila sleep research, with a focus on neural structures and the genetic basis of sleep regulation.